Exploitation of treatment induced tumor lysis to enhance the sensitivity of ctDNA analysis: A first-in-human pilot study. (March 2022) - Breadner, Daniel A.; Vincent, Mark D.; Correa, Rohann; Black, Morgan; Warner, Andrew; Sanatani, Michael; Bhat, Vasudeva; Morris, Clive; Jones, Greg; Allan, Alison; Palma, David A.; Raphael, Jacques
Highlights: ctDNA levels increase in the hours to days after starting a new treatment. Testing ctDNA in the hours after starting treatment increases sensitivity. Testing hours after treatment may reveal mutations that were occult pre-treatment. Abstract: Introduction: Blood-based liquid biopsies examining circulating tumour DNA (ctDNA) have increasing applications in non-small cell lung cancer (NSCLC). Limitations in sensitivity remain a barrier to ctDNA replacing tissue-based testing. We hypothesized that testing immediately after starting treatment would yield an increased abundance of ctDNA in plasma because of tumor lysis, allowing for the detection of genetic alterations that were occult in baseline testing. Methods: Three prospective cohorts of patients with stage III/IV NSCLC were enrolled. Cohort 1 (C1) contained patients starting platinum doublet chemoradiation (n = 10) and cohort 2 (C2) initiating platinum doublet cytotoxic chemotherapy ± immunotherapy (n = 10). Cohort 3 (C3) contained patients receiving palliative radiation. Two baseline samples were collected. In C1 and C2, subsequent samples were collected 3, 6, 24 and 48 h post initiation of chemotherapy. Patients in C3 had samples collected immediately prior to the next three radiotherapy fractions. Samples were analyzed for ctDNA using the 36-gene amplicon-based NGS Inivata InVisionFirst®-Lung assay. Results: A total of 40 patients were enrolled. Detectable ctDNA was present at baseline in 32 patients (80%), 4 additional patients (50%) had detectable ctDNA in post-treatment samples. Seven patients with detectable ctDNA at baseline (23%) had new genetic alterations detected in post-treatment samples. Mutant molecule numbers increased with treatment in 24 of 31 (77%) pts with detectable ctDNA. ctDNA levels peaked a median of 7 h (IQR:2–26 h) after the initiation of chemotherapy and a median of 2 days (IQR:1–3 days) after radiation was commenced. Conclusion: ctDNA levels increase in the hours to days after starting treatment. ctDNA testing in the acute post-treatment phase can yield results that were not evident in pre-treatment testing. Application of this principle could improve ctDNA utility as an alternate to tissue-based testing and improve sensitivity for the detection of treatment-resistant clones.(NCT03986463).